The spatial heterogeneity of micro- and meio-organisms and their significance in understanding coastal system dynamics. (30th November 2018) - Kirsten, Kelly L.; Fell, Jessica; Frenzel, Peter; Meschner, Stephanie; Kasper, Thomas; Wündsch, Michael; Meadows, Michael; Haberzettl, Torsten
Abstract: An array of sediment surface samples collected from the coastal lake Eilandvlei and its bar-built estuary, on the southern Cape coast, South Africa were analysed for their micro- and meio-organism diversity to understand the complexity in their distribution in relation to their habitat and in response to physicochemical parameters. The variation in the diatom community proved to be a useful proxy in tracking the movement of various source waters, namely riverine inputs and marine throughflow. Particularly, the transport and deposition of freshwater diatom species are shown to represent the inflow of riverine waters into the lake, revealing internal current flow and a dispersal pattern of inputs. A comprehensive documentation of ostracods and foraminifera was undertaken for the system. Habitat-specific factors, such as pH, macrophyte extent and water depth, are the primary determinant for these species distribution. The combination of these organisms provides information on the provenance of the organisms and assists in distinguishing allochthonous versus autochthonous assemblages. This study shows that biological assemblages are useful indicators of system functionality, even in the most complex environments, when recorded environmental data is absent. Highlights: Lake samples analysed for their micro- and meio-community, hitherto undocumented. Understand how certain biological organisms co-exist and function in the system. Determine the distribution of the biota in relation to their habitat, physicochemical parameters. Provides insights into the taphonomic processes at play in the coastal system. Distinguishing autochthonous from allochthonous assemblage.